2021 год. Осенняя сессия, 25 ноября - 14 декабря - Дяченко Людмила Петровна (2023)
Экземпляры: КХ (20241004) / Инвентарный номер: 1130037 / Сис.шифр: 67.400 / Авт.знак: Г 72 / ГРНТИ: 10 / ББК: 67.400.621